The role of stomata and its importance in resistance of Acasia synophyla trees to gas air pollutants - Janoud, Najat (Latakia University Journal -Basic Sciences Series, 2018)
The present research was conducted to study the resistance of Acasia tree which were near to Banias- Jableh freeway. This study was performed by study the stomata and its distribution on the upper and down leaf surfaces. Also, a concentration of chlorophyll and a severity of photosynthesis, then compared the results between the polluted region with the control one. Results showed that a number of stomata decreased in polluted region compared to the control one, where this reduction play a role in reduce the injury resulting from gas air pollutants, and this reflexes on the severity of photosynthesis and the chlorophyll.